Cereals and their economic value - O'Daniel, Mary Lorena (My University, 1904)
Introduction: Of all the plants now so universally diffused over the surface of the globe the grasses are of the first importance to man. From them he derives all.the essentials of life. The cereals embracing a portion only of the family of grasses are to man in his civilized condition more important than the other classes of grasses. They contain the elements to form bone, muscle and fat.
Citation: O'Daniel, Mary Lorena. Cereals and their economic value. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Cereals; Grains; Grasses; History of Grains; Nutrition of Grains; Theses